The development of myGeo-RS: A knowledge management system of geodiversity data for tourism industries - Deraman, Aziz; Yahaya, Jamaiah; Salim, Juhana; Idris, Sufian; Jambari, Dian Indrayati; Jaradat, Asraf; Komoo, Ibrahim; Leman, Mohd Shafeea; Unjah, Tanot; Sarman, Marilah; Lim, Choon Sian (IBIMA Publishing, 2009)
The development of MyGeo-RS, a geodiversity information and repository system is a valuable solution that can assure the management and preservation of geological datasets more interesting, accessible and shared to the public at large. This research is embarked based on the realization that with the advancement of information and communication technology, as well as data mining and knowledge discovery, knowledge about geodiversity can be better represented and explored.This project attempts to establish on how geodiversity components and their relationships can be modeled into various forms of digital object (DO) to enable access and sharing of geodiversity information. The target user groups of this project are mainly to public users and tourism industry.This paper presents the research objectives,research approach, system analysis and myGeo-RS architecture.